Outcomes and characteristics of patients on protease inhibitors at a tertiary level antiretroviral clinic - Michele Perks; Denasha L. Reddy; Francois Venter (AOSIS, 2023)
Background: Protease inhibitors (PIs) have been recommended as World Health Organization second-line antiretroviral therapy (ART) for low- to middle-income countries for two decades. As dolutegravir-based regimens have become widely available, the future role of PIs is uncertain. Objectives: To describe the characteristics of patients on PI-based ART (in first-line and second-line regimens), double-boosted protease inhibitors (DBPI) and patients who received recycled nucleoside reverse transcriptase inhibitors (NRTI) in second-line regimens at a tertiary level ART clinic. Method: We conducted a descriptive retrospective record review of adult patients on PI-based ART who attended Nthabiseng Adult Infectious Diseases Clinic at Chris Hani Baragwanath Academic Hospital in Soweto, South Africa, between January 2021 and April 2022. Results: Of the 900 patients sampled, 543 (60.3%) were female, the median age was 45 and 703 (79.1%) had viral loads (VL) below 1000 copies/mL. In contrast, 21 (58.3%) of 36 vertically infected patients had VLs below 1000 copies/mL. Thirty-seven (4.1%) patients were on DBPIs. The commonest reason for DBPI use in 24 (64.9%) patients was drug resistance test (DRT)-guided switch after virological failure. Forty-nine (5.4%) patients were on recycled NRTIs with no DRT, and 24 (2.6%) patients were on NRTIs to which there was documented resistance. Outcomes for these patients were similar to the total sample. Conclusion: PIs have long been a cornerstone of second-line ART. This study demonstrates the real-world utility of PIs, as well as their disadvantages. There was no difference in the outcomes of patients who received recycled NRTIs in second-line regimens.